Effectiveness of treatment of a patient for the first time diagnosed pulmonary tuberculosis with concomitant pathology depending on the method of administration of antimycobacterial drugs - M. M. Kuzhko; N. M. Gulchuk; O. V. Avramchuk; T. V. Tlustova (Civic Union "Communicable Diseases Intensive Care Association", 2019)
Resume. The use of antimycobacterial therapy in its majority leads to a positive dynamics of the TB disease, smear and sputum cultures conversion and cure of the patient. The lack of an expected positive response to the therapy happens in a limited number of patients. One of the most common reason for the lack of a positive response, in the conditions of the appointment of therapeutic agents in accordance with the identified sensitivity and controlled use of chemotherapy, may be the presence of concomitant pathology and malabsorption / maldigestia syndrome. Your attention is given to the clinical case of the progression of pulmonary tuberculosis on the background of oral administration of antimycobacterial drugs. During the treatment, the presence of chronic pancreatitis and malabsorption syndrome of oral forms of drugs was confirmed, which allowed changing the treatment tactics and reaching the patient's cure.